Competency Development, Sustainability Practices, and Industry Preparedness in Maritime Vocational Education - Winarno Winarno; Tri Cahyadi; Larsen Barasa; Aji Permana; Cris Kuntadi; Yayu Nopriani Martha; Marudut Bernadtua Simanjuntak (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates the effectiveness of maritime vocational education in preparing graduates to meet the evolving demands of the industry, focusing on competency development, sustainability integration, and practical readiness. The research addresses the increasing need for training programs to align with global industry standards while incorporating sustainable practices to manage environmental and operational challenges. By integrating insights from maritime professionals, educators, graduates, and regulatory officers, the study provides a comprehensive and grounded analysis. The research explores how maritime education equips graduates with industry-relevant skills and incorporates sustainability into training frameworks. Using a qualitative approach, the study involved interviews with 10 stakeholders and thematic analysis of their experiences. Findings indicate strong outcomes in practical readiness (score: 9.3/10), supported by immersive sea-going experiences and hands-on training. However, sustainability integration scored lower (8.6/10), highlighting the need for a greater emphasis on environmental practices and sustainable operations within curricula. The results underscore the significance of collaboration between educational institutions and industry professionals to ensure training aligns with real-world demands. This study offers valuable recommendations for curriculum design and sustainability practices, contributing to a well-prepared and environmentally conscious maritime workforce. The findings serve as a foundation for policy development, institutional strategies, and further research into vocational training and sustainable maritime operations.